The Jews of Yemen in light of the excavation of the Jewish synagogue in Qanī’ (poster) - Tobi, Yosef (Proceedings of the Seminar for Arabian Studies, 2013)
This paper draws attention to the genuine (i.e. not converted) Jewish community that lived in many localities all over the Himyari kingdom, such as Ẓafār, the capital of that kingdom, Ḥaṣī in the south, and Qanī’ in the south-east. The various archaeological and epigraphic findings of the last fifty years illustrate a typical Jewish community of the time. The Greek inscription found at the synagogue in Qanī’ has enriched our knowledge of the Jews of Ḥimyar, not only from the standpoint of new details that were obtained, but also by shedding light on certain anecdotes that were previously known by us but not fully comprehended. We may conclude that the Jewish community in the Kingdom of Himyar — even prior to the Judaization of the kingdom — appears to have been a vital one, having all essential religious and social institutions, just as any other Jewish community in other countries.